CORAL REEF FISHES IN THE COASTAL WATERS OF SOUTH-CENTRAL VIETNAM - Long, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2009)
Studies on coral reef fishes in the coastal waters of South Central Vietnam were conducted at 42 sites of coral reefs at the four major locations of Van Phong Bay, Nha Trang Bay, Ninh Hai - Ninh Thuan and Ca Na Bay from 2006 - 2007, and combined with available data of species composition from previous studies. A total of 578 species representing 180 genera and 40 families of coral reef fishes was recorded. The analysis and comparison indicate that diversity of coral reef fish fauna in the coastal waters of South Central Vietnam was higher than that in other locations in the coastal waters of Vietnam (the Tonkin Gulf, southeastern and southwestern waters of Vietnam), more or less similar to that in the Spratly Islands and many other locations around the world. In the coastal waters of South Central Vietnam, Nha Trang Bay supported a higher diversity and abundance of most of fish families than Van Phong Bay, Ninh Hai - Ninh Thuan and Ca Na Bay.